Skilled interpersonal communication research, theory and practice - Hargie, Owen (Abingdon, Oxon Routledge, 2022)
Established as the foremost textbook on communication, the seventh edition of Owen Hargie's Skilled Interpersonal Communication is thoroughly revised and updated with the latest research findings, theoretical developments and applications.

The contribution of skilled interpersonal communication to success in both personal and professional contexts is now widely recognised and extensively researched. People have a deep-seated and universal need to interact with others, and the greater their communicative ability the more satisfying and rewarding will be their lives. The main focus of this book is on the identification, analysis and evaluation of the core skills needed in these interactions. The first two chapters provide details of the nature of interpersonal communication and socially skilled performance respectively, with a review of the main theoretical perspectives pertaining to each. The book then offers detailed accounts of the fourteen main skill areas: nonverbal communication; reinforcement; questioning; reflecting; listening; explaining; self-disclosure; set induction; closure; assertiveness; influencing; negotiating; and, interacting in and leading group discussions. The book concludes with a discussion on the ethical issues in interpersonal communication. This new edition also features an extended section on groupthink and analyses the impact of the coronavirus pandemic on aspects such as greeting patterns and the effectiveness of Project Fear by the UK government to secure citizen compliance.

Written by one of the foremost international experts in the field, this is essential reading for students of interpersonal communication in general, and to qualified personnel and trainees in many fields.-- Provided by publisher.
The Feature of interpersonal communication -- A Conceptual model of skilled interpersonal communication -- Communicating without words: skilled nonverbal behaviour -- Rewarding others: the skill of reinforcing -- Finding out about others: the skill of questioning -- Showing understanding for others: the skill of reflecting -- Paying attention to others: the skill of listening -- Getting your message across: the skill of explaining -- Telling others about yourself: the skill of self-disclosure -- Opening and closing interactions: the skills of set induction and closure -- Standing up for yourself: the skill of assertiveness -- Using your influence: the skill of persuasion -- Working things out together: the skills of negotiating -- Working with others: skills of participating in and leading small groups -- Concluding comments.
Includes bibliographical references and index.
Keywords: Interpersonal communication